Validation of the PROMIS® measures of self-efficacy for managing chronic conditions - Gruber-Baldini, Ann L.; Velozo, Craig; Romero, Sergio; Shulman, Lisa M. (Quality of life research, 2017)
Purpose The Patient-Reported Outcomes Measurement Information System® (PROMIS®) was designed to develop, validate, and standardize item banks to measure key domains of physical, mental, and social health in chronic conditions. This paper reports the calibration and validation testing of the PROMIS Self-Efficacy for Managing Chronic Conditions measures. Methods PROMIS Self-Efficacy for Managing Chronic Conditions item banks comprise five domains, Self-Efficacy for Managing: Daily Activities, Symptoms, Medications and Treatments, Emotions, and Social Interactions. Banks were calibrated in 1087 subjects from two data sources: 837 patients with chronic neurologic conditions (epilepsy, multiple sclerosis, neuropathy, Parkinson disease, and stroke) and 250 subjects from an online Internet sample of adults with general chronic conditions. Scores were compared with one legacy scale: Self-Efficacy for Managing Chronic Disease 6-Item scale (SEMCD6) and five PROMIS short forms: Global Health (Physical and Mental), Physical Function, Fatigue, Depression, and Anxiety. Results The sample was 57% female, mean age=53.8 (SD=14.7), 76% white, 21% African American, 6% Hispanic, and 76% with greater than high school education. Full-item banks were created for each domain. All measures had good internal consistency and correlated well with SEMCD6 (r=0.56-0.75). Significant correlations were seen between the Self-Efficacy measures and other PROMIS short forms (r >0.38). Conclusions The newly developed PROMIS Self-Efficacy for Managing Chronic Conditions measures include five domains of self-efficacy that were calibrated across diverse chronic conditions and show good internal consistency and cross-sectional validity.